Comparison Of Physical Fitness Levels Of Students Of SMPN 3 Kabun With Students Of MTs Al Amin Bencah Kesuma, Kabun District - Rodhiyah, Nur Afifah; Putra, Riwaldi; Putra, Muarif Arhas (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
Physical fitness is the ability of the human body to perform heavy or light activities that are carried out repeatedly to meet the needs of movement in daily activities without experiencing fatigue. This study aims to determine the comparison of the level of physical fitness of students of SMP N 3 Kabun with MTS Al-Amin Bencah Kesuma. This study uses a comparative method through a quantitative descriptive approach. The population in this study were all students of SMP N 3 Kabun Bencah Kesuma 101 students, and all students of MTS A-l Amin Bencah Kesuma Village 118 students. Sampling used the purposive sampling method so that the total sample was 48 students consisting of 24 students of class VIII SMP N 3 Kabun and 24 students of MTS Al-Amin Bencah Kesuma. In this study TKJI (Indonesian Physical Fitness Test). The results of the study showed that the level of physical fitness of male students at SMP N 3 Kabun was in the moderate category with a percentage of 28.57%. While male students at MTs Al-Amin Boncah Kesuma are in the moderate category with a percentage of 78.57%. There is a difference in the level of physical fitness of male students between SMP N 3 Kabun and MTs Al-Amin Boncah Kesuma by 46%. Female students at SMP N 3 Kabun are in the good category with a percentage of 60%. And female students at MTs Al-Amin Boncah Kesuma are in the moderate category with a percentage of 70%. There is a difference in the level of physical fitness of female students between SMP N 3 Kabun and MTs Al-Amin Boncah Kesuma by 9%.